The application of 1920s Bauhaus aesthetic to contemporary album design - Ma, Thia (My University, 2022)
The aesthetic choices for this design reinforce the central idea of 3 into 1. Three individuals on three different instruments come together to become the Up and Over Trio. The three colours leading into the Trio's title demonstrate this relationship and signify the importance of each musician's sound. Conversely, take one colour away, and the design loses its balance. Red, blue, and yellow is used because, as primary colours, they create all other colours. Considering the Trio's history of playing back up, these essential colours show they are the focus of this album. Using simple shapes in the typeface and visual design elements keeps the overall feel of the cover clean and modern. The textured background adds visual interest and grounds the overall design, making it approachable and warm. Additionally, the brown paper texture is reminiscent of a wrapped gift waiting to be opened and enjoyed. The 3D placement of the text and colours adds visual rhythm, not unlike jazz music, in a contemporary style that is playfully unexpected. The typeface used throughout deliverables is Joost, a typeface intended to emulate the 1920s design aesthetic. It's pulling from the age of jazz while still appealing to modern audiences. The black type, in particular, stands out against the textured background and boldly draws the eye. The final design honours the Trio, their paths that led to the creation of this album, and the evolving world of jazz.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta.
Keywords: album design; graphic design; Bauhaus